2016
DOI: 10.1166/jnn.2016.12704
|View full text |Cite
|
Sign up to set email alerts
|

Research on Interface Structure During Nanowelding with Molecular Dynamics and Experimental Method

Abstract: The mechanism of nanowelding between single-walled carbon nanotubes (SWNTs) and Ni substrate was investigated by molecular dynamics (MD) and experimental method. The horizontal oriented nanowelding system composed of metal electrode and SWNT subsystem was built for simulation study. The dynamic process of nanowelding was described completely at atomistic length scales, and the evolution of welding interface structure under different temperature and time was revealed by MD method. Simulation results showed nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Beside the in-situ method to investigate the properties of the nanomaterial that can be performed experimentally [6], MD simulation has shown its ability in the investigation of these properties. Some researchers have indicates that the data obtained by the MD simulation also have shown good agreement with the experimental works [82,83,94,95,[86][87][88][89][90][91][92][93]. Therefore, using MD simulation to investigate those properties is reasonable, either in its good agreement or to reduce the cost of research, and also there are broad ranges of techniques to make sure that the MD simulation performed is could be validated [96] to maintain its correctness.…”
Section: Estimation Of Mechanical Electrical and Thermal Properties/p...mentioning
confidence: 96%
See 1 more Smart Citation
“…Beside the in-situ method to investigate the properties of the nanomaterial that can be performed experimentally [6], MD simulation has shown its ability in the investigation of these properties. Some researchers have indicates that the data obtained by the MD simulation also have shown good agreement with the experimental works [82,83,94,95,[86][87][88][89][90][91][92][93]. Therefore, using MD simulation to investigate those properties is reasonable, either in its good agreement or to reduce the cost of research, and also there are broad ranges of techniques to make sure that the MD simulation performed is could be validated [96] to maintain its correctness.…”
Section: Estimation Of Mechanical Electrical and Thermal Properties/p...mentioning
confidence: 96%
“…This process is demonstrated in Figure 8(a). Meanwhile, specific nano-welding from CNT onto Ni substrate has been demonstrated by Liu et al [82]. They have shown that the nanowelding of CNT and the Ni substrate could be accomplished at a temperature of 1500 K which is below the melting point of Ni (1726 K).…”
Section: Other Applicationmentioning
confidence: 99%
“…The method of MD simulation is mainly built by the solution of the Newtonian equation of motion numerically which runs under a particular ensemble of atoms where can be used to investigate the material behaviors [16][17][18][19][20][21][22][23][24][25][26][27][28][29]. In the application of diffusion welding, there are several investigations using MD simulation like, Chen et al when perform an investigation of diffusion bonding between Cu-Ag [5] and Cu-Al [6] which revealing the mechanism of diffusion bonding and shed light on the importance of pressure, temperature, and surface roughness on the process.…”
Section: mentioning
confidence: 99%
“…The capability of handling various broad applications of materials investigations and the advantages offered by MD simulation has led many studies to adopt this method, including those that were conducted to figure out the influence of several parameters in various welding techniques that are critical during the process of welding and their impact on the mechanical properties. Specifically for the diffusion welding process, MD simulation has shown great results, which not only revealed atomistic behavior, as it can be visualized by several software tools [4,5], but some mechanical properties can also be estimated and validated by this method [6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%